Advances in Cognitive Translation Studies
X, 220 p. 30 illus., 15 illus. in color.
Keywords: This book presents the latest theoretical and empirical advances in cognitive translation studies. It involves the modes of written translation, interpreting, sight translation, and computer-aided translation. In separate chapters, this book proposes a new analytical framework for studying keylogged translation processes, a framework that reconciles a sociological and a psychological approach for studying expertise in translation, and a pedagogical model of translation competence. It expands the investigation of cognitive processes by considering the role of emotional factors, reviews, and develops the effort models of interpreting as a didactic construct. The empirical studies in this book revolve around cognitive load and effort; they explore the influences of text factors (e.g., metaphors, complex lexical items, directionality) while taking into account translator factors and evaluate the user experience of computer-aided translation tools.